BRIDGING THE GREY DIGITAL DIVIDE: SOCIETAL CHANGE FROM 2002 TO 2014 IN GERMANY. (16th November 2018) - Huxhold, O; Hees, E; Webster, N
Abstract: The internet is an indispensable aspect of modern society. It facilitates long distance communication, access to information, health care interactions, as well as multiple opportunities for social participation. Despite increasing pervasiveness of this technology persistent inequalities exist in who has access to the internet, an important and understudied precursor to use. In particular, older adults lag behind in having access to the internet, thus putting them at risk for social exclusion. In order to gain more information on this grey digital divide the current study contrasts influencing factors of internet access, comparing samples from 2002 and 2014 across age groups (40 to 54 years, 55 to 69 years and 70 to 85 years) using data from the German Ageing Survey (DEAS). Logistic regression confirms the hypothesis of internet access declining with age at both time points. However, the percentages of people with internet access grew between 2002 and 2014, especially in the middle and older age groups. Furthermore, being male and having a higher education were associated with greater odds of internet access. Nevertheless, gender and education differences in internet access decreased with time. Finally, both greater income and cognitive ability were associated with greater odds of internet access, while providing care for a grandchild was a significant predictor for internet access only among the oldest age group. In an attempt to bridge the grey digital divide the current study serves as a basis for identifying groups mostly affected by this form of inequality and indicates possible resources for intervention.